Apple polyphenols improve intestinal barrier function by enhancing antioxidant capacity and suppressing inflammation in weaning piglets. (14th June 2022) - Guo, Zhongyang; Chen, Xiaoling; Huang, Zhiqing; Chen, Daiwen; Yu, Jie; Yan, Hui; Chen, Hong; He, Jun; Zheng, Ping; Luo, Yuheng; Yu, Bing
Abstract: This study aimed to examine the effects of apple polyphenols (APPs) on antioxidant capacity, immune and inflammatory response, and barrier function in weaning piglets. Results showed that APPs improved jejunal barrier function by increasing the villus height, villus height/crypt depth, the mRNA levels of occludin, mucin‐1, and mucin‐4 and up‐regulating the protein expression of occluding ( P  < 0.05). As for antioxidant capacity, APPs increased the activities of total superoxide dismutase and glutathione peroxidase and total antioxidant capacity level in jejunum ( P  < 0.05). Besides, APPs up‐regulated the protein expressions of NAD(P)H quinone dehydrogenase 1 (NQO1), heme oxygenase‐1 (HO‐1), and nuclear‐related factor 2 (NRF2) and down‐regulated the protein expression of kelch‐like ECH‐associated protein 1 (Keap1). As regard to immune and inflammatory response, APPs increased the immunoglobulin A content in serum and decreased the mRNA levels of tumor necrosis factor‐α ( TNF‐α ), interleukin ( IL ) ‐1β, toll‐like receptor 4 ( TLR4 ), nuclear factor‐κB ( NF‐κB ), and IL‐8 in jejunum ( P  < 0.05). Overall, dietary APPs supplementation improves the jejunal barrier function by enhancing antioxidant capacity and suppressing the mRNA expression related to inflammation, which may be related to the NRF2 signal and TLR4/NF‐κB signal.